Investigating the validity of the short form Burnout Assessment Tool: A job demands-resources approach - Leon T. de Beer; Wilmar B. Schaufeli; Arnold B. Bakker (African Journal of Psychological Assessment, 2022)
The purpose of this study was to investigate the psychometric properties of the short form Burnout Assessment Tool (BAT-12). As a result of the pandemic, job stress has been compounded and the use of conceptually grounded and accurate measures is needed to identify burnout risks within specific organisations and the overall workforce. The study sample comprised 660 employees from various occupational settings who filled out an online survey. Latent variable methods with ordinal categorical data were implemented to model the data and to test the hypotheses for the study. Results showed that the proposed second-order factor model of the BAT-12 showed a good fit to the data and was invariant across gender and ethnicity. In addition, burnout – as operationalised with the BAT-12 – played the hypothesised mediating role in the Job Demands-Resources model. The BAT-12 also showed convergent validity with the Maslach Burnout Inventory. The authors conclude that BAT-12 is a robust instrument with adequate psychometric properties to measure burnout risk and present a freely available online application for employees to estimate their risk of burnout.